Pengaruh Inovasi Produk dan Inovasi Proses Terhadap Keunggulan Bersaing dan Kinerja Pemasaran UMKM Produk Camilan - Ahmad, Alifian Rizzalul; Wahyuni, Lia Kusuma (Majalah Ilmiah DIAN ILMU, 2023)
Micro, Small and Medium Enterprises (MSMEs) play an important rolein Indonesia's economic growth by increasing income or employmentopportunities. MSMEs contribute significantly to Indonesia's economic growthby creating jobs that produce goods and services that society needs. Thisresearch aims to determine the influence of product innovation and processinnovation on the competitive advantage and marketing performance ofMSMEs for snack products in Jember Regency. This research uses quantitativeresearch methods. The total population in this study is MSMEs for snackproducts in the Jember Regency area as reflected by the respondent owners,while the number of samples in this study is 50 MSMEs which were obtainedusing the Ferdinand formula. The results of this research are that productinnovation has no significant effect on competitive advantage, processinnovation has a significant positive effect on competitive advantage,competitive advantage has a significant positive effect on marketingperformance, the interaction of product innovation and process innovation oncompetitive advantage weakens marketing performance.